Ab initio study of the surface properties of austenitic stainless steel alloys - Pitkanen H; Alatalo M; Puisto A; Ropo M; Kokko K; Vitos L (ELSEVIER SCIENCE BV, 2022)
Using ab initio calculations we investigated the surface energies of paramagnetic Fe1-c-nCrcNin random alloys within the concentration range of 0.12 <= c <= 032 and 0.04 <= n <= 0.32. These alloys crystallize mainly in the face centred cubic (fcc) structure and constitute the main building blocks of austenitic stainless steels. It is shown that all alloys have the lowest surface energies along the most close packed crystal orientation, namely the fcc (111) surfaces. The amount of Ni seems to have little effect on the surface energy, while almost all composition-driven change may be attributed to the changes in the Cr content. Within the studied compositional range, the change of the surface energy with the composition is of the order of 10%. Trends of the surface energy can be related to the magnetic structure of surfaces. Using the total energy as a function of the concentration, we determine the effective chemical potentials in bulk and at the surface, which can be used to estimate the surface segregation energies. (C) 2012 Elsevier B.V. All rights reserved.